H19X-encoded microRNAs induced by IL-4 in adipocyte precursors regulate proliferation to facilitate differentiation - Choijamts Munkhzul; Ji-Min Lee; Boseon Kim; Thi Thanh My Nguyen; Rehna Paula Ginting; Dahee Jeong; Young-Kook Kim; Min-Woo Lee; Mihye Lee (Biology Direct, 2023)
Abstract Adipose tissue, an organ critical for systemic energy homeostasis, is influenced by type 2 immunity in its development and function. The type 2 cytokine interleukin (IL)-4 induces the proliferation of bipotential adipocyte precursors (APs) in white fat tissue and primes these cells for differentiation into beige adipocytes, which are specialized for thermogenesis. However, the underlying mechanisms have not yet been comprehensively examined. Here, we identified six microRNA (miRNA) genes upregulated upon IL-4 stimulation in APs, miR-322, miR-503, miR-351, miR-542, miR-450a, and miR-450b; these are encoded in the H19X locus of the genome. Their expression is positively regulated by the transcription factor Klf4, whose expression also increases upon IL-4 stimulation. These miRNAs shared a large set of target genes, of which 381 genes were downregulated in mRNA expression upon IL-4 stimulation and enriched in Wnt signaling pathways. Two genes with downregulated expression, Ccnd1 and Fzd6, were repressed by H19X-encoded miRNAs. Additionally, the Wnt signaling activator LiCl downregulated the expression of this group of miRNAs in APs, indicating that Wnt signaling–related genes and these miRNAs form a double-negative feedback regulatory loop. This miRNA/Wnt feedback regulation modulated the elevated proliferation of APs induced by IL-4 stimulation and contributed to priming them for beige adipocyte differentiation. Moreover, the aberrant expression of these miRNAs attenuates the differentiation of APs into beige adipocytes. Collectively, our results suggest that H19X-encoded miRNAs facilitate the transition of APs from proliferation to differentiation in the IL-4-mediated regulation.